Erratum to: Probing the mixing between sterile and tau neutrinos in the SHiP experiment - Ki-Young Choi; Sung Hyun Kim; Yeong Gyun Kim; Kang Young Lee; Kyong Sei Lee; Byung Do Park; Jong Yoon Sohn; Seong Moon Yoo; Chun Sil Yoon (Journal of High Energy Physics)
A correction to this paper has been published: https://doi.org/10.1007/JHEP06(2024)166